Development and application of a method for quantifying factors affecting chloramine decay in service reservoirs - Sathasivan, Arumugam; Bal Krishna, K.C.; Fisher, I. (Elsevier Science Ltd, 2010)
Service reservoirs play an important role in maintaining water quality in distribution systems. Several factors affect the reservoir water quality, including bulk water reactions, stratification, sediment accumulation and wall reactions. It is generally thought that biofilm and sediments can harbour microorganisms, especially in chloraminated reservoirs, but their impact on disinfectant loss on disinfectant loss has not been quantified. Hence, debate exists as to the extent of the problem. To quantify the impact, the reservoir acceleration factor (FRa) is defined. This factor represents the acceleration of chloramine decay arising from all causes, including changes in retention time, assuming that the reservoir is completely mixed. Such an approach quantifies the impact of factors, other than chemical reactions, in the bulk water. Data from three full-scale chloraminated service reservoirs in distribution systems of Sydney, Australia, were analysed to demonstrate the generality of the method. Results showed that in two large service reservoirs (404 × 103 m3 and 82 × 103 m3) there was minimal impact from biofilm/sediment. However, in a small reservoir (3 × 103 m3), the biofilm/sediment had significant impact. In both small and large reservoirs, the effect of stratification was significant.